Optimisation of COPD exacerbation management and follow-up: a clinical audit - Eloise Rogers; Begum Bingor; Maryama Warfa; Ahmed Hossain; Maria Fotiou; Rawan Elkalaawy; Sinem Sahin; Zahra Jahangir; Amir Jehangir (Clinical Medicine, 2025)
Introduction: Chronic obstructive pulmonary disease (COPD) exacerbations are the second most common cause of emergency hospital admissions, often leading to repeated presentations and poor patient outcomes.1 Evidence-based guidelines (National Institute of Health and Care Excellence (NICE), Global Initiative for Chronic Obstructive Lung Disease (GOLD) and British Thoracic Society (BTS)] provide recommendations for the management of COPD exacerbations, including assessment, diagnosis, acute and long-term management, and appropriate follow-up.2–4This audit aimed to assess compliance with current guidelines in the management and follow-up of COPD exacerbations at University College Hospital (UCH), London, to identify areas requiring an intervention for improvement. Materials and Methods: A retrospective analysis of COPD exacerbation cases presenting to the emergency department (ED) and acute medical unit (AMU) in UCH was conducted over a 2-month period. 37 patients were initially identified for analysis. Data on pre-admission, inpatient management and discharge practices were collected from electronic patient records and benchmarked against national guidelines. Once areas of poor compliance were identified, educational sessions were designed and presented to resident doctors to highlight these areas. Additionally, an electronic ‘COPD checklist’ smartphrase was created and presented to the resident doctors to serve as a prompt within documentation (Fig 1). A re-audit was conducted over a 2-week period, identifying 20 cases for analysis to assess the impact of the intervention. Results and Discussion: In the first cycle of data collection, poor compliance was observed in three principal areas. Smoking cessation advice/referral was offered in 62% of cases, vaccination status was documented in 14%, and outpatient follow-up referrals were requested in 38%. Following the intervention with educational sessions and smartphrase introduction, the re-audit showed marked improvements. Smoking cessation advice/referrals increased to 67%, vaccination status documentation to 50%, GP follow-up referrals to 85%, and respiratory follow-up referrals to 50% (Fig 2). The COPD checklist was adopted in 35% of cases.Initial results reported distinct areas of poor compliance with COPD guidelines in UCH. The reasons are likely multifactorial, but could include a lack of awareness of national guidelines in resident doctors and inconsistent documentation. Literature shows that providing educational interventions contributes to continuing professional development and improves patient outcomes.5 While adherence to the smartphrase use remained suboptimal, adherence to documentation of its components in accordance with guidelines significantly increased during the re-audit period following educational sessions.A major limitation faced during this audit was case identification: our electronic patient records lacked standardised coding for COPD exacerbation admissions, which created difficulty in identifying appropriate admissions for analysis. Other limitations included a short re-audit period (2 months vs 2 weeks), inconsistent documentation and staff availability for teaching sessions. Future audit cycles could benefit from longer audit cycles, more accessible educational sessions and analysis of long-term implications by investigating rate of readmissions. Conclusion: COPD exacerbations are frequently encountered in acute care settings, but guideline adherence remains challenging. This audit demonstrates targeted interventions, such as staff education and structured checklists, are effective ways to standardise documentation and improve compliance with COPD guidelines. The marked improvements observed at UCH are likely indicative of gains achievable across other UK hospitals. Reinforcing national guidelines in acute care can standardise management and potentially improve patient outcomes.